Application of the WHO Method of Workload Indicators of Staffing Needs to Evaluate Health Workers Availability and Capacity for Universal Health Coverage in Maternal and Child Health in Benin - Sossou, Justin Adanmavokin; Sossou, Gilles-Armand; Igué, Babatoundé Charlemagne; OUENDO, EDGARD-MARIUS DONA (My University, 2020)
To assess the operational capacity of human resources in maternal and child health services, in order to provide equitable and sustainable universal health coverage in Benin, the Workload Indicators of Staffing Need (WISN) study was conducted. Method: A total of 487 health facilities and public hospitals were sampled, representing 75% of the public health facilities. Health professionals involved in maternal and child health care were exhaustively included. Results: Overall, 487 health facilities with 3,870 human resources of all categories were evaluated for their workloads. The analysis shows that the country does not have the necessary manpower to handle the workload. The time spent by the health professional on activities changes according to the type of activity. Finally, it is noted that there is work pressure on health professionals which changes according to the type of activity. Discussion: The shortage situation leads to inequity in the distribution of human resources and is a reason for allocative and technical inefficiency. It is observed that qualified human resources devote little working time to the main activities, which explains the observed high morbidity and mortality rates, particularly for mothers and children. In conclusion, the analysis of the results shows that the pressure of work is greater in rural areas than in urban areas for the professional categories most encountered in rural areas and that the health system is fragile in the country.
Keywords: WISN; Labor Pressure; Equity; Maternal and Child Health; Universal Health Coverage; Availability of Human Resources for Health; Benin Republic